2001
DOI: 10.1086/324650
|View full text |Cite
|
Sign up to set email alerts
|

A Genomewide Search for Quantitative-Trait Loci Underlying Asthma

Abstract: A genomewide screen for quantitative-trait loci (QTLs) that underlie asthma was performed on 533 Chinese families with asthma, by the unified Haseman-Elston method. Nine asthma-related phenotypes were studied, including forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), airway responsiveness as indicated by methacholine (MTCH)-challenge test, serum total immunoglobulin E (TIgE), serum-specific immunoglobulin E, eosinophil count in peripheral blood, and skin-prick tests with three different al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 24 publications
2
55
2
Order By: Relevance
“…This is in agreement with other phenotypic studies, which have shown that FEV1 does not systematically strongly correlate with disease symptoms [2,17]. Moreover, none of the published genome-wide screens conducted for lung function in asthmatic families reported linkage to the 2p23 region, detected here for the asthma severity score [18][19][20]. Taken together, these results indicate that FEV1 (% pred) is more likely to be controlled by specific genetic determinants.…”
Section: Phenotype Definition and Linkage Analysis Outcomessupporting
confidence: 92%
“…This is in agreement with other phenotypic studies, which have shown that FEV1 does not systematically strongly correlate with disease symptoms [2,17]. Moreover, none of the published genome-wide screens conducted for lung function in asthmatic families reported linkage to the 2p23 region, detected here for the asthma severity score [18][19][20]. Taken together, these results indicate that FEV1 (% pred) is more likely to be controlled by specific genetic determinants.…”
Section: Phenotype Definition and Linkage Analysis Outcomessupporting
confidence: 92%
“…A genome-wide study of the French population failed to detect a linkage to asthma but detected linkage to eosinophilia around the 130 cM region (Dizier et al 2000). There was no evidence of linkage to asthma-related phenotypes of chromosome 12 markers in the Chinese population, which is ethnically close to the Japanese population (Xu et al 2001b). In combination, the results of our and previous studies suggest that several genes located in 12q24-q33 are likely to be responsible for susceptibility to asthma.…”
Section: Discussioncontrasting
confidence: 53%
“…On the other hand, many studies have shown negative linkage for total IgE. These include studies of the Australian population by Daniels et al (1996), the Germans by Heinzmann et al (2000a), the Germans and Swedish by Wjst et al (1999), the Hutterites by Ober et al (2000), the Chinese by Xu et al (2001b), the French by Dizier et al (2000), the Finnish by Leitinen et al (2001), the Italians by Malerba et al (2000), and the Danish by Haagerup et al (2002). This inconstancy suggests that the relative importance of chromosome 12 loci in controlling total IgE varies from population to population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a second-stage analysis among a subset of the CSGA AfricanAmerican families, strong evidence for linkage has been observed at 11q21 (80). Follow-up fine-mapping studies have narrowed the critical linkage region to one containing several interesting candidates, including CD44, EHF, ELF5, and GSTP1 (81,82).…”
Section: Update On Genetic Studies Of Asthma In Populations Of Africamentioning
confidence: 99%